A bone-targeting delivery system carrying osteogenic phytomolecule icaritin prevents osteoporosis in mice. (November 2018) - Huang, Le; Wang, Xinluan; Cao, Huijuan; Li, Ling; Chow, Dick Ho-Kiu; Tian, Li; Wu, Heng; Zhang, Jiayong; Wang, Nan; Zheng, Lizhen; Yao, Xinsheng; Yang, Zhijun; et al.
Abstract: Targeting delivery system has been widely used in packaging drugs for medical therapies attributed to its high efficiency and efficacy. A Traditional Chinese Medicine (TCM) formula consisting of Herba Epimedii has previously been shown to effectively treat postmenopausal osteoporosis. We have subsequently found that icaritin, which was a flavonoid isolated from both Herba Epimedii and its serum metabolites after oral administration, inhibited the adipogenic capacity of bone mesenchymal stem cells (BMSCs) while promoted their osteogenesis. However, previous pharmacokinetic analyses have shown that icaritin had a short half-life in blood and only trace amounts of the molecule reach the bone tissue. To overcome this limitation, we developed a bone-targeting liposome containing an oligopeptide of eight aspartate residues (Asp8), which had previously been shown to specifically target the bone, encapsulating icaritin. In vivo, we found that the Asp8-icaritin-liposome enhanced bone formation in ovariectomized mice compared to an icaritin-liposome control lacking the Asp8 moiety. Through in vitro mechanistic studies we further found that icaritin inhibited adipogenesis through an Akt/GSK-3β/β-catenin signaling pathway. Taken together, our study shows that Asp8-liposome as a bone-targeting delivery system is effective to carry an osteogenic phytomolecule for facilitating and enhancing its therapeutic effects on the prevention of estrogen depletion-induced osteoporosis.